Ecological shifts of stream ecosystems in a deglaciating area of the European Alps - Brighenti, Stefano (Università degli studi di Trento, 2019)
This thesis provides a contribution to the knowledge on the effects of deglaciation on alpine stream ecosystems, taking into account also the hydroecological influence of thawing permafrost and paraglacial features. With a focus on the European Alps, a review is provided on the climate changes and shifts in the cryosphere (snow, glaciers, permafrost), the related changes in hydrology, geomorphic processes and the physical and chemical habitat of alpine river networks, and the consequent shifts in stream communities and food webs. A conceptual model is provided to summarize the complex interactions and the cascading effects triggered by deglaciation on hydrology, habitat and biota of alpine streams, that can be useful for educational purposes and to help the scientific community to contextualize these issues to other alpine areas. Deglaciation induces homogenisation of river networks, loss of biodiversity, and shifts in primary and secondary production, functional diversity and food webs. The scarce published studies on streams influenced by permafrost provide hints on the role of thawing rock glaciers (i.e. evident form of mountain permafrost) in shaping the ecology of freshwaters, and reveal important research gaps. To increase the knowledge on this topic, different alpine streams fed by waters of different origin were selected in two subcatchments (Zay, Solda) of a deglaciating area of the Central Italian Alps (Solda Valley), and their habitat conditions and benthic invertebrate communities were investigated over a two-year period. Rock glacier-fed streams could be distinguished from those fed by glaciers, groundwater and those of mixed origin because of their constantly clear and very cold waters, stable channels, and high concentrations of ions and trace elements that increased as summer progressed. Furthermore, the Zay rock glacier strongly influenced the glacier-fed stream through an intense export of solutes, which become progressively more relevant towards the end of summer. This influence was also due ...